Determining the maximally permissible values for the indicators of insulation of sealed entrance bushings with a voltage of 110 kV using the method of minimal risk - Shutenko, O. V.; Zagaynova, A. A.; Serdyukova, G. N. (PC тесhnology сеntеr, 2018)
A method for determining the maximally permissible values for the indicators of insulation of high-voltage oilfilled entrance bushings that ensure the minimal risk value has been proposed. The proposed method differs in that the maximally permissible values for indicators are determined by minimizing the function of average risk, using the Newton’s method, taking into consideration the actual operating conditions of equipment, which makes it possible to improve the operational reliability of entrance bushings. We have derived an expression to determine the average risk with respect to the distribution law of indicators for the insulation of high-voltage entrance bushings (by Weibull), the minimization of which makes it possible to determine the maximally permissible values for the indicators, taking into consideration the duration of their operation, the values of load currents, the grade of a transformer oil, and other factors. A comparative analysis was performed for risk values, which are accompanied by applying the maximally permissible values for indicators that are regulated in Ukraine, with the maximally permissible values for indicators, which were obtained by using different methods. The analysis revealed that the minimal risk value is ensured by the maximally permissible values for indicators, which are obtained by applying the method of minimal risk, taking into consideration the operating conditions for entrance bushings. We have performed an analysis of impact of the values for probabilities of the proper-functioning and faulty state of entrance bushings, the cost of incorrect decisions, as well as the value for a scale parameter and a shape parameter in the Weibull distribution, on the maximally permissible values for the indicators of insulation of high-voltage oil-filled entrance bushings in an airtight structure. It was established that an increase in the probability of a defect and its conditional cost, as well as prolonging the operation duration of entrance bushings and their loading, leads to a decrease in the maximally permissible values for the indicators. It has been proven that the maximally permissible values for the indicators of insulation of high-voltage entrance bushings, which ensure the minimal economic loss, are not constant. In order to practically implement the method of minimal risk during operation, it has been proposed to apply the likelihood ratios, which make it possible to diagnose the state of high-voltage entrance bushings at a minimal risk, but without determining the maximally permissible values for the indicators.

Запропоновано метод визначення гранично допустимих значень показників ізоляції високовольтних маслонаповнених вводів, які забезпечують мінімальне значення ризику. Пропонований метод відрізняється тим, що гранично допустимі значення показників визначаються шляхом мінімізації функції середнього ризику, методом Ньютона, з урахуванням реальних умов експлуатації обладнання, що дозволяє підвищити експлуатаційну надійність вводів. Отримано вираз для визначення середнього ризику з урахуванням закону розподілу показників ізоляції високовольтних вводів (Вейбулла), мінімізація якого дозволяє визначати гранично допустимі значення показників, з урахуванням їх терміну експлуатації, значення струмів завантаження, сорту трансформаторного масла і інших чинників. Виконано порівняльний аналіз значень ризиків, які супроводжуються використанням гранично допустимих значень показників, регламентованих в Україні, з гранично допустимими значеннями показників, які отримані різними методами. Аналіз показав, що мінімальне значення ризиків забезпечують гранично допустимі значення показників, які отримані методом мінімального ризику з урахуванням умов експлуатації вводів. Виконано аналіз впливу значень ймовірностей справного і дефектного стану вводів, вартостей помилкових рішень, а також значення параметрів масштабу і форми розподілу Вейбулла на гранично допустимі значення показників ізоляції високовольтних маслонаповнених вводів герметичній конструкції. Встановлено, що збільшення ймовірності виникнення дефекту і його умовної вартості, а також збільшення терміну експлуатації вводів і завантаження призводить до зниження гранично допустимих значень показників. Доведено, що гранично допустимі значення показників ізоляції високовольтних вводів, що забезпечують мінімум економічних збитків, не є постійними. Для практичної реалізації методу мінімального ризику в процесі експлуатації запропоновано використовувати відношення правдоподібності, які дозволяють виконувати діагностику стану високовольтних вводів з мінімальним ризиком, але без визначення гранично допустимих значень показників.
Визначення гранично передбачених значень показників ізоляції герметичних вводів 110 кВ методом мінімального ризику
Keywords: high voltage entrance bushing; insulation indicators; minimal risk; probabilities of erroneous and correct decisions; Weibull distribution; likelihood ratios; високовольтний ввід; розподіл Вейбулла; відношення правдоподібності; напруга; електрична енергія